Effectiveness of a training programme to improve hand hygiene compliance in primary healthcare - García-Ferradal Inmaculada; Arnal-Selfa Rosa; Abanades-Herranz Juan; Salinero- Fort Miguel; Cañada-Dorado Asunción; Martín-Madrazo Carmen; Espejo-Matorral Flora; Santa-Pau Enrique; Soto-Diaz Sonia (BMC, 2009)
Abstract Background Hand hygiene is the most effective measure for preventing infections related to healthcare, and its impact on the reduction of these infections is estimated at 50%. Non-compliance has been highlighted in several studies in hospitals, although none have been carried out in primary healthcare. Main objective To evaluated the effect of a "Hand Hygiene for the reduction of healthcare-associated infections" training program for primary healthcare workers, measured by variation from correct hand hygiene compliance, according to regulatory and specific criteria, 6 months after the baseline, in the intervention group (group receiving a training program) and in the control group (a usual clinical practice). Secondary objectives -To describe knowledges, attitudes and behaviors as regards hand hygiene among the professionals, and their possible association with "professional burnout", stratifying the results by type of group (intervention and usual clinical practice). -To estimate the logistic regression model that best explains hand hygiene compliance. Methods/Design Experimental study of parallel groups, with a control group, and random assignment by Health Center. Area of study.- Health centers in north-eastern Madrid (Spain). Sample studied.- Healthcare workers (physicians, odontostomatologists, pediatricians, nurses, dental hygienists, midwife and nursing auxiliaries). Intervention.- A hand hygiene training program, including a theoretical-practical workshop, provision of alcohol-based solutions and a reminder strategy in the workplace. Other variables: sociodemographic and professional knowledges, attitudes, and behaviors with regard to hand hygiene. Statistical Analysis: descriptive and inferential, using multivariate methods (covariance analysis and logistic regression). Discussion This study will provide valuable information on the prevalence of hand hygiene non-compliance, and improve healthcare.